Influence of pH in Obtaining Indium Tin Oxide Nanoparticles by Microwave Assisted Sovothermal Method - Borges de Oliveira, Fernando Modesto; Varela, Jose Arana [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2018)
A systematic study about synthesis of In1-xSnxO2 (ITO) n) nno structured crystals by microwaveassistd solvothermal method is repor.ted Different solutionsinusmg In.l(3) OH(2)0 and Sn.l(4) 5H(2)0 precursors in ethylene glycol solvent were prepared in distinct pHs (acid and basic on.es) The syntheses were performed at degrees 0 degrees Cinusmg a hinatmg rate of degrees 0 degrees in(-1)mm(1) and soaking time of 30 minu.tes All the synthesized powders were characterized by X-ray Diffraction (XRD) and Rietveld refinement to study the phase evolution as a function of. pH The materials synthesized in the pH ranging between. 115 and. 119 were further studied by field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) techniq.ues As ITO matenals have many practical applications due to their transpareniny m the visible spectrum, UV-Vis spectroscopy analysis was performed to obtain the optical band gap and the respective optical window.
Keywords: ITO; nanoparticles; Microwave-assisted solvothermal; optical properties